The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1590/s0101-81751994000400003
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica da reprodução do cascudo, Rineloricaria latirostris Boulenger (Siluriformes, Loricariidae) do rio Passa Cinco, Ipeúna, São Paulo

Abstract: ABSTRACT. REPRODUC' TION DYNAMICS 01'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 2 publications
1
5
0
5
Order By: Relevance
“…The values for GSI also began to rise in August/September, peaking in October/November for females and August/September for males. Similar results were found in other Loricariidae in various regions of Brazil, for example, Rhinelepis aspera (Agostinho et al, 1990), Hypostomus commersonii (Agostinho et al, 1991), H. ancistroides (Viana et al, 2008), Rineloricaria latirostris (Barbieri, 1994), Loricariichthys platymetopon (Bailly et al, 2011;Marcucci et al, 2005), L. spixii (Duarte et al, 2007), among others. Males showed distinctly greater condition factor than that of females throughout the study period, probably because of higher energy expenditure of females during the maturation process (Cantanhêde et al, 2007), a feature also reported by Agostinho et al (1990) for Rhinelepis aspera in the rio Paranapanema (state of Paraná).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The values for GSI also began to rise in August/September, peaking in October/November for females and August/September for males. Similar results were found in other Loricariidae in various regions of Brazil, for example, Rhinelepis aspera (Agostinho et al, 1990), Hypostomus commersonii (Agostinho et al, 1991), H. ancistroides (Viana et al, 2008), Rineloricaria latirostris (Barbieri, 1994), Loricariichthys platymetopon (Bailly et al, 2011;Marcucci et al, 2005), L. spixii (Duarte et al, 2007), among others. Males showed distinctly greater condition factor than that of females throughout the study period, probably because of higher energy expenditure of females during the maturation process (Cantanhêde et al, 2007), a feature also reported by Agostinho et al (1990) for Rhinelepis aspera in the rio Paranapanema (state of Paraná).…”
Section: Discussionsupporting
confidence: 81%
“…Studies addressing population and reproductive aspects of this family of fish have been conducted in several Brazilian basins, focusing on several species such as Rhinelepis aspera Spix & Agassiz, 1829 (Agostinho et al, 1987;Agostinho et al, 1990), Hypostomus commersonii Valenciennes, 1836 (Agostinho et al, 1991), Rineloricaria latirostris (Boulenger, 1900) (Barbieri, 1994), Hypostomus ancistroides (Ihering, 1911) (Viana et al, 2008), Pareiorhina rudolphi (Miranda Ribeiro, 1911) (Braga et al, 2009), among others. Studies conducted on the genus Loricariichthys have focused primarily on L. anus (Valenciennes, 1835), L. platymetopon Isbrücker & Nijssen, 1979(Tos et al, 1997Querol et al, 2002;Marcucci et al, 2005;Bailly et al, 2011) and L. spixii (Steindachner 1881) (Duarte & Araújo, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los ovarios maduros estudiados presentaron características similares a las de otros loricaridos con ovocitos maduros "grandes" por poseer gran cantidad de vitelo, lo que también explica, como ya se dijo, la baja fecundidad encontrada (MachadoAllison, 1993;Barbieri, 1994;Suzuki, 2000). La distribución de las frecuencias de los diámetros ovocitarios representadas en la figura 1, con dos picos o grupos predominantes de ovocitos, develan un crecimiento ovocitario por grupos de maduración o asincrónico, otros loricaridos también lo presentan Pachyurus bonariensis y Loricariichthys platymetopon (Marcucci et al, 2005).…”
Section: Discussionunclassified
“…Los ovocitos liberados fueron tamizados en malla de nylon de 500 µm de ojo de malla siendo que los retenidos por la malla, considerados como ovocitos "reclutados", esto es en alguna etapa de maduración vitelogénica y que efectivamente pueden ser expulsado en un próximo desove, fueron contados manualmente (Barbieri, 1994). Con la suma de los ovocitos retenidos de los dos ovarios de cada hembra se estableció la Fecundidad.…”
Section: Materiales Y Métodosunclassified